Synthesis, characterization and elucidating the role of secondary coordination sphere in transition metal-based calixpyrrole and salixpyrrole complexes - Ahmed, Md Tofayel (My University, 2025)
Climate change has become a burning issue due to its increasing severe impacts on the environment. The largest contributor to climate change is global greenhouse gas emissions from burning fossil fuels. It is hypothesized that higher temperatures, increase in sea level, severe storms, loss of species, increased drought, scarcity of food, health threats are the consequences of the ongoing climate change. To combat these negative impacts, hydrogen is a favorable alternative fuel source as this is a clean and environmentally benign energy source with the highest gravimetric energy density compared to all the chemical fuels. Researchers have been inspired by hydrogenase enzymes and efforts have been made to mimic the catalytic active site of this biological system. In view of this, three nickel-based calixpyrrole complexes were reported with various amino pendant groups (NHC(O)CH₃ and NHC(O)OC(CH₃)₃) and non-pendant group in the secondary coordination sphere. All three complexes displayed some catalytic activity for HER in the presence of anilinium tetrafluoroborate as a proton source. However, these catalysts performed poorly compared to the previously reported nickel calixpyrrole catalyst with pendant amine groups. These complexes lack stability under the reaction conditions and exhibited pronounced sensitivity to the scanning window. Upon removal of the complex from the solution, rinse test results showed rapid decomposition of the heterogeneous catalytic species. These results provide important insights into the design of molecular catalyst for HER that pendant hydrogen donor/acceptor moieties are not sufficient to regulate local proton transport in interfacial environments. It is extremely important to incorporate a group in the secondary coordination sphere that can shuttle protons from the reaction medium to the electrode surface. A novel monometallic palladium salixpyrrole complex was synthesized following Schiff-base reaction and using calixpyrrole starting material and salicylaldehyde. The 1H NMR and single crystal X-ray crystallography data matched with a previously reported unsymmetric cofacial salixpyrrole catalyst which is catalytically efficient for HER. Homo- and hetero-bimetallic salixpyrrole systems should be synthesized, fully characterized, and electrochemical studies should be carried out to fully elucidate the reactivity and mechanism towards HER.
Keywords: Calixpyrrole; Proton shuttle; Secondary coordination sphere